Traditional Chinese medicine for lupus nephritis: modulation of autoimmune pathogenesis - Huang, Zhiyan; Li, Xiaolong; Zhu, Qingmiao; Zhu, Mengyu; Fan, Yongsheng; Zhao, Ting (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceLupus nephritis (LN) is an immune complex glomerulonephritis commonly associated with systemic lupus erythematosus. Traditional Chinese medicine (TCM) has emerged as a promising adjuvant therapy for LN, due to its low toxicity and diverse therapeutic effects for long-term management.Materials and methodsA comprehensive search of PubMed and Web of Science was conducted up to 7 June 2024, using keywords related to lupus nephritis, traditional Chinese medicine, immune cells, and kidney resident cells. Study quality were assessed based on Good Automated Manufacturing Practice guidelines, with evaluations jointly conducted by two authors.ResultsThis review includes 31 research papers and summarizes seven herbal formulas and 18 phytochemicals that modulate the autoimmune pathogenesis of LN. Their mechanisms involve regulating immune cells activation, differentiation, apoptosis, as well as influencing resident kidney cells to support renal protection and immune homeostasis. Since TCM exhibit bidirectional regulation, they activate regulatory immune cells while suppress pathogenic factors. Inconsistent or inconclusive findings are discussed.ConclusionThis review summarizes current research on herbal formulas and phytochemicals in immune cells and kidney resident cells in LN, highlighting the potential and significance of TCM treatment. It also addresses the limitations of existing studies and suggests that future research should focus on exploring the immunosuppressive and kidney-protective effects of herbal formulas and phytochemicals, as well as enhancing the clinical translation and standardization of TCM.